Cambridge handbook of routine dynamics - Feldman, Martha S. 1953-; Pentland, Brian T.; D'Adderio, Luciana; Dittrich, Katharina 1983-; Rerup, Claus ca. 20. Jh; Seidl, David 1971- (Cambridge University Press, 2021)
Over the last two decades, Routine Dynamics has emerged as an international research community that shares a particular approach to organizational phenomena. At the heart of this approach is an interest in examining the emergence, reproduction, replication and change of routines as recognizable patterns of actions. In contrast to other research communities interested in those phenomena, Routine Dynamics studies are informed by a distinctive set of theories (especially practice theory and related process-informed theories). This Handbook offers both an accessible introduction to core concepts and approaches in Routine Dynamics as well as a comprehensive and authoritative overview of research in different areas of Routine Dynamics. The chapters of this Handbook are structured around four core themes: 1) Theoretical resources for research on the dynamics of routines, 2) Methodological issues in studying the dynamics routines, 3) Themes in Routine Dynamics research and 4) Relation of Routine Dynamics to other communities of thought